Pengembangan Game Edukasi Berbasis GDevelop untuk Meningkatkan Pemahaman Murid dalam Materi Sistem Komputer - Valerian Permana Sukma; Alfadl Habibie; Muhammad Taufiq (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
This study aims to develop and test the effectiveness of GDevelop-based educational games in improving students' understanding of computer systems material. The research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed product is an interactive educational game featuring a Pair Game concept, where students match computer component images with their corresponding descriptions or functions, complemented by a quiz system and immediate feedback mechanism. The research subjects consisted of grade X students from SMAN 3 Kota Tasikmalaya. Data were collected through validation by media experts and material experts, learning outcome tests (pre-test and post-test), and student response questionnaires. The findings revealed that the media obtained a feasibility score of 81% from media experts and 75% from material experts, both falling within the highly feasible category. The effectiveness test demonstrated a significant increase in student understanding with an N-Gain value of 0.73, categorized as high. The GDevelop-based educational game proved to be feasible and effective as a learning medium for enhancing students' understanding of computer systems material.